Recent results on conserved charge fluctuations in ALICE - Arslandok, Mesut (Nuclear physics. A, Nuclear and hadronic physics, 2021)
Recent results on the analysis of event-by-event net-baryon number fluctuations in Pb-Pb collisions at √sNN=2.76 and 5.02 TeV are presented. The cumulants of the net-proton distributions, proxies for the net-baryon distributions, up to third order are discussed. The experimental results are compared with HIJING and EPOS model calculations and the dependence of fluctuation measurements on the phase-space coverage is addressed in the context of calculations from Lattice QCD (LQCD) and the Hadron Resonance Gas (HRG) model.
Available online: 10 December 2020
Gesehen am 28.01.2021